Effects of Impulsivity and Interpersonal Problems on Adolescent Depression: A Cross-Lagged Study - Yang, Yanan; Tian, Mingyangjia; Liu, Yu; Qiu, Shaojie; Hu, Yuan; Yang, Yang; Wang, Chenxu; Xu, Zhansheng; Lin, Lin (Behavioral sciences, 2024)
The dynamic changes over time in the relationships between impulsivity, interpersonal problems, and depression warrant further exploration. This study delves into the roles of impulsivity and interpersonal issues in the progression of adolescent depression over a year, using a sample of 271 Chinese adolescents (51.7% male, Mage = 12.60 ± 0.69). At three time points, impulsivity levels were assessed with the Chinese version of the Barratt Impulsiveness Scale-11, interpersonal problems with the Adolescent Self-Rating Life Events Check List, and depression with the Center for Epidemiologic Studies Depression Scale. Results revealed that both impulsivity and interpersonal problems serve as risk factors for depression, but the primary risk factor shifted over time. In early middle school stages, impulsivity was the predominant risk factor, while in later stages, interpersonal problems became the primary risk factor. These findings carry significant implications for directing prevention efforts and interventions for adolescent depression.